Integration of information resources of open access to provide the scientific and educational process in the institutions of higher education - Dmitriy A. Kachan; Alexandra V. Bogatko; Ivan N. Bogatko; Sergei V. Enin; Uladzimir G. Kulazhanka; Vladimir S. Lazarev; Pavel A. Lis; Alexey V. Skalaban; Ina V. Yuryk (Открытое образование (Москва))
Purpose of the study. The purpose of this paper is to analyze the current state and prospects for introducing the principles of open access to scientific publications and scientific data in the sphere of science and education in Belarus. Its relevance is related to the need to develop measures to accelerate the process of digital transformation of science and education of the Republic of Belarus.Materials and methods. Information base of the research was made by publications of scientists and specialists on the issues under study, normative documents, final documents of conferences on this topic, data from the Open Data in Belarus portal, national and international aggregators of institutional repositories, open scientific data repositories.Results. The analysis of the state and prospects of introducing the principles of open access to scientific publications and scientific data into the sphere of science and education of Belarus was carried out during the research. It is shown that the digital transformation of science and education is at an early stage. The dissemination of the principles of open science and the introduction of new instruments of scientific communication in the Belarusian academic and university science are uneven, there is a need to develop a strategy in this direction. The principle of open access to publications is being most actively introduced into practice through the development of a network of university repositories. In Belarus, the open data infrastructure is at the very beginning of its formation. In this regard, there is a need to conduct additional research to identify problems associated with the discovery of scientific data. One step in the transition to open science is the unification of all the repositories on a single platform of the national aggregator. The review of national and international aggregators of institutional repositories is presented. The questions on creation of the national system-aggregator of information resources of open access in the Republic of Belarus in the context of the formation of the Republican information and educational environment are considered: the purpose of the system, the platform used, technical solutions for organizing the integration of information systems of higher education institutions and the rules of interaction of system users.Conclusions. The creation of a national system-aggregator will not only provide a single point of access to the institutional repositories of project participants, which will significantly improve the convenience and completeness of the search, but will also solve one of the most important tasks of the project - popularizing the idea of open access to scientific publications. The implementation of the proposed measures to create conditions for the discovery of scientific data in Belarus will contribute to the introduction of the principle of open access to scientific data. The considered approaches will allow accelerating the process of digital transformation of the scientific and educational sphere of Belarus.